2020
DOI: 10.1080/17435390.2020.1814440
|View full text |Cite
|
Sign up to set email alerts
|

Human hazard potential of nanocellulose: quantitative insights from the literature

Abstract: This review aims to elucidate the current knowledge and future research needs regarding the hazard potential of nanocellulose to human health. Growing interest from research and industry alike has led to increasing likelihood of human contact to the material via various exposure routes. Although a number of comprehensive reviews on human health hazards of nanocellulose have been conducted, this paper brings new insights as it systematically analyzes and quantitatively assesses the results of in vivo and in vit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 55 publications
1
39
0
Order By: Relevance
“…Generally, nanocellulose is considered to be biocompatible (no or low cytotoxicity), while recent studies reported that nanocellulose has been shown to exert toxic effects in tissue culture systems. [12][13][14] The nanocellulose effects on the liver, where biomedical use of nanocellulose as drug delivery carriers will be accumulated due to liver filtration function, has not been performed. We found that the shorter nanocellulose samples (including CNC-1, CNC-2, and CNC-3), not the longer nanocellulose samples (including CNF-1 and CNF-2), triggered significant cytotoxicity in KCs due to their differential cellular uptake; However, only CNC-2 induced slight toxicity in hepatocytes due to its less cellular uptake.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Generally, nanocellulose is considered to be biocompatible (no or low cytotoxicity), while recent studies reported that nanocellulose has been shown to exert toxic effects in tissue culture systems. [12][13][14] The nanocellulose effects on the liver, where biomedical use of nanocellulose as drug delivery carriers will be accumulated due to liver filtration function, has not been performed. We found that the shorter nanocellulose samples (including CNC-1, CNC-2, and CNC-3), not the longer nanocellulose samples (including CNF-1 and CNF-2), triggered significant cytotoxicity in KCs due to their differential cellular uptake; However, only CNC-2 induced slight toxicity in hepatocytes due to its less cellular uptake.…”
Section: Discussionmentioning
confidence: 99%
“…Although nanocellulose is generally regarded as safe based on its biocompatibility as well as biodegradability and the great majority of studies have pointed to the absence of significant cytotoxic effects by a vast diversity of CNC samples from different origins and with diverse properties in many mammalian cell lines, recent studies have been reported that nanocellulose displayed the adverse effects in vitro and in vivo. [ 11–14 ] For example, the CNCs in the 200–300 nm length scales have been shown to induce significant lysosomal damage, NLRP3 inflammasome activation as well as IL‐1β production in the human myeloid cell line, THP‐1. [ 15 ] Also, Yanamala et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, no statistically significant increase of in cells or nucleoplasmatic bridges were detected in specimens exposed to 1.25 g/L of CNS in artificial freshwater, compared to the control (data not shown). We remind that, despite an absence of genotoxic effects revealed by the nanomaterial (CNS) used in the present in vivo experimental conditions, the inhalation of nano-scaled cellulose may have adverse effects on human health, especially related to pulmonary exposure and because of its potential bio-persistence when inhaled [ 63 ]. However, there is a scarcity of chronic, low dose, and repeated exposure studies, making occupational exposure risk assessment of the various life stages of nanocellulose-containing products difficult [ 63 ].…”
Section: Resultsmentioning
confidence: 99%
“…NC human hazard potential literature on in vivo and in vitro tests has been reviewed by focusing on cellulose nanoparticles and nanofibers functionalized or not [4]. Even though a large part of in vitro tests shows no cytotoxicity, regarding in vivo testing there are still significant uncertainties remaining due to the scarcity of the studies that do not allow reaching the rational of a satisfying structure-property relationship.…”
Section: Introductionmentioning
confidence: 99%